2001
DOI: 10.3168/jds.s0022-0302(01)74621-8
|View full text |Cite
|
Sign up to set email alerts
|

Tail-Docking Alters Fly Numbers, Fly-avoidance behaviors, and Cleanliness, but not Physiological Measures

Abstract: Tail docking is an animal well-being issue not only regarding the docking procedures but also because of concerns during fly season. To address the latter question, we selected eight cows that had been tail-docked in a previous experiment and eight nondocked cows matched by stage of lactation. Physiological, immunological, and behavioral measures were used to evaluate the well being of those cows housed in a tie-stall barn during fly season for 5 consecutive days. Behavior was observed for 5-min interval insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 19 publications
1
44
0
1
Order By: Relevance
“…Little merit was found for docking with regard to health or hygiene, although there were differences between cows (Tucker et al, 2001). Tail-docking research by Purdue University scientists and USDA-ARS Livetock Behavior Research Center from 1997 to the present demonstrated that cow and heifer well-being can be compromised by acute pain, increased sensitivity, or chronic pain in the stump, as well as increased fly numbers and irritation (Eicher et al, 2001;Eicher and Dailey, 2002). The American Veterinary Association (AVMA, 2005) is officially opposed to tail-docking.…”
Section: Tail-dockingmentioning
confidence: 93%
See 1 more Smart Citation
“…Little merit was found for docking with regard to health or hygiene, although there were differences between cows (Tucker et al, 2001). Tail-docking research by Purdue University scientists and USDA-ARS Livetock Behavior Research Center from 1997 to the present demonstrated that cow and heifer well-being can be compromised by acute pain, increased sensitivity, or chronic pain in the stump, as well as increased fly numbers and irritation (Eicher et al, 2001;Eicher and Dailey, 2002). The American Veterinary Association (AVMA, 2005) is officially opposed to tail-docking.…”
Section: Tail-dockingmentioning
confidence: 93%
“…Tail-docking and SCC are often mentioned in association with one another, although docking does not significantly affect SCC (Eicher et aL, 2001;Schreiner and Ruegg, 2002). Dairies with tail-docked cows had an average SCC of 223,000 cells/mL as compared with nondocked cows at 237,000 cells/mL (P = 0.95).…”
Section: Tail-dockingmentioning
confidence: 99%
“…However, the effect of docking is not clearly demonstrated. Depending on studied indices, either no difference was found between docked and undocked dairy cows in udder cleanliness or health (Tucker et al, 2001) or docked cows were found to be cleaner than undocked ones (Eicher et al, 2001). On the other hand, docked cows have more flies due to a significant increase in fly numbers on the rear legs.…”
Section: Lefebvre Lips ö Dberg and Giffroymentioning
confidence: 96%
“…Tail swings were the most frequent fly-avoidance behaviour recorded in intact cows. Finally, docked cows stood more and exhibited increased general restlessness than intact cows when the fly numbers increased, indicating that they were uncomfortable (Eicher et al, 2001;Eicher and Dailey, 2002).…”
Section: Lefebvre Lips ö Dberg and Giffroymentioning
confidence: 99%
“…Those practices with more than 10% of respondents reporting negative implications for welfare were feeding of a GMO-free diet, feeding of an organic diet, the use of antibiotics for sick animals, tail docking and dehorning. Given that numerous studies have reported welfare problems, such as pain in cattle as a function of tail docking and dehorning [18] [19] [20] [21], respondents' views of these as impinging on cow welfare were unsurprising. The views that feeding (GMO-free) diets that are often publicly lauded as safer, healthier or more sustainable [22], and treating of ill animals with antibiotics negatively impacted cattle welfare were unexpected and difficult to explain.…”
Section: Perceptions Of Dairy Cattle Management Practicesmentioning
confidence: 99%